The Effect of Self-Efficacy and Subjective Norms on Entrepreneurial Intention with Entrepreneurial Attitude as an Intervening Variable - Alisyahbana, Andi Naila Quin Azisah; Isma, Andika (Pinisi Journal of Entrepreneurship Review, 2025)
Entrepreneurship plays a crucial role in realizing the vision of “Golden Indonesia 2045,” with university students expected to act as agents of change through strong entrepreneurial intentions. This study aims to examine the effect of self-efficacy and subjective norms on entrepreneurial intention, with an entrepreneurial attitude serving as a mediating variable. The study employed a quantitative approach using path analysis. Data was collected through questionnaires distributed to 105 undergraduate students and analyzed statistically. The results reveal that self-efficacy has a positive and significant effect on entrepreneurial intention, both directly and indirectly through an entrepreneurial attitude. Although subjective norms do not directly influence entrepreneurial intention significantly, they have a positive and significant indirect effect mediated by entrepreneurial attitude. Furthermore, entrepreneurial attitude itself significantly influences entrepreneurial intention. These findings highlight the importance of developing both personal efficacy and supportive social environments to foster positive entrepreneurial attitudes, which in turn enhance entrepreneurial intention among university students. The study provides valuable insights for educational institutions and policymakers to design effective entrepreneurship education and support systems.